Outcome of the workshop about prospects and knowledge needs for improving soil organic carbon in Vietnam, 5 July 2019 - Tran Minh, T.; Vu Manh, Q.; Tran Thi Minh T.; Vu Hong, H.; Zaiss, R; Jouquet, P. (DataSuds, 2021)
This dataset holds the outcome of the regional workshop prospects and knowledge needs for improving soil organic carbon in Vietnam. The workshop was organized at the Soils and Fertilizers Research Institute (SFRI) on July 5th 2019 with the support of CIRCASA and IRD office in Hanoi. More than 30 participants from many different organizations including government, universities, institutes, NGOs, extension services, farmer association participated at this workshop. They are working in the agricultural-related field so that they can share the experiences, knowledge, difficulties and solutions about the issue of soil organic carbon (SOC) management.